ANALISIS INTERAKSI SOSIAL ASOSIATIF PADA WIRAUSAHA IKAN ARWANA - Triana Triana; Sulistyarini Sulistyarini; Izhar Salim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
ABSTRACTThe goal of this research was to know the associative social interaction in forms of cooperation and accommodation of arowana fish entrepreneurs at Tanjung Village in Suhaid Sub-district of Kapuas Hulu District. The method used was qualitative method with descriptive analysis. The data collection tools were observation guidelines, interview guidelines, and documentation tools. The data analysis techniques used were datareduction, data presentation, decision making, and verification. The results were (1) the associative social interaction in form of the traditional cooperation in arowana fish entrepreneurs at Tanjung Village in Suhaid Sub-district of Kapuas Hulu District, was evident in M. Amin, Saleh, Ruslan, Sunardi and Syah Bandi who helped each other in theprocess of fishing in other areas in Kapuas Hulu, in the process of marketing fish to costumers in several areas, in the process of fish packaging ordered by customers in Pontianak, in the process of delivering fish to Pontianak, in the process of arowana fish contest at PCC building in Pontianak; (2) the associative social interaction in form of thecompromise accommodation in arowana fish entrepreneurs at Tanjung Village in Suhaid Sub-district of Kapuas Hulu District, was proven in Ruslan and Sunardi in finding solutions to their entrepreneurship problems through discussion.Keywords:Arowana Fish Entrepreneur, Social Interaction.